نظام الذكاء الاقتصادي وأثره في تحقيق تنافسية منظمات الأعمال واستدامتها - د. الشاذلي عيسى حمد عبد الله; د. فضيلة بوطورة (White Nile Journal for Studies and Research, 2021)
It is clear from this research paper the role of economic intelligence in supporting and enhancing competitive capabilities by achieving a competitive advantage for organizations, as modern business organizations are trying to meet competitive challenges and global environmental changes by adopting the method of economic intelligence as a prerequisite for continuously improving their operations, developing their performance and identifying their capabilities. The Ministry of Interior, based on the performance of the leading organizations in their field of activity, and working to reduce the gap between them and the organizations that are at the fore in order to ensure their survival, growth and continuity. To achieve the goal of the study, the researchers conducted a descriptive and analytical study of the role of economic intelligence in promoting competitiveness and its sustainability for business organizations, by discussing the following points: the general framework of economic intelligence, the basics of competitive advantage, economic intelligence and achieving competitive advantage. Finally, the study demonstrated the effectiveness of economic intelligence in Achieving and maintaining this advantage, with the recommendation that Arab countries should adopt technology, development and creativity in this field in order to be able to win the bet of this successful system in the field of business and the economies of countries. Keywords: economic intelligence, information, competitive advantage, business organizations, competitiveness, sustainability, sustainable competitive advantage.